BUDAYA ORGANISASI (STUDI EKSPLORASI PADA UNIVERSITAS MUHAMMADIYAH SEMARANG) - -, Triyono (VALUE ADDED | MAJALAH EKONOMI DAN BISNIS, 2012)
This research is aimed to explore the organization behavior of Universitas Muhammadiyah Semarang. It includes the observation and opinion of the lecturers, employees and alumni of Universitas Muhammadiyah Semarang about the leadership, the norm and management practices, the story and legend, the tradition and the symbols which are exist on the organization. This research used qualitative method. The method of collecting the data was done by interview, observation, and literature study. Those methods were done to get more specific data about the organization behavior of Unimus. The objects of this research were supporting documents (decree, photonovela), interview with the employees who have been working at Unimus for 10 years, and other documents which support the organization behavior. The result shows that some of the organization behavior elements, the norms of leadership and management practices, the story and legend, the tradition and ritual, and the symbols are appropriate with the organization behavior expected by Universitas Muhammadiyah Semarang. The respondents’ opinions are expected to give the characteristics of the organization behavior of that institution. The advantage of implementation of the organization behavior is to strengthen construction value of the organization behavior at Universitas Muhammadiyah Semarang.